(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Hydroxychloroquine (HCQ) has been found to have antithrombotic, lipid-lowering and glucoselowering properties that make it useful in treating a variety of chronic diseases, including rheumatoid arthritis and systemic lupus erythematosus. Recently various study also showed its anti proteinuric andrenoprotective effects. To evaluate the effecacy of HCQ as an add on to the conventional therapy of Diabetic Nephropathy (DN). Materials and methods: This open label randomized controlled trial was conducted at the Chittagong Medical College Hospital in Chattogram at the Nephrology Department. Sixty patients of DN were enrolled as per selection criteria into two groups, in one group 30 patients were started HCQ (100 mg twice daily) along with conventional treatment of DN (Experimental group). In other group 30 patients were started with conventional treatment without HCQ (Control group). They were followed up after 3 rd and 6 th month of initiation of the treatment. Both groups were followed upfor any significant changes in their renal function, proteinuria, glycaemic status and lipid profile. Results: At the end of six months there was almost 8.9% reduction of serum creatinine in experimental group while it increased in control group around 22.2% both of which were significant (p<0.001). In contrast, eGFR increased by almost 9.9% in experimental group and decreased by 15% in control group which were also statistically significant (p<0.001).The proportion of patients who had >30% reduction of proteinuria after six months in the experimental and control groups was 50% and 6.7%, respectively (p<0.001). After 6 months, serum cholesterol declined significantly (24.76±30.82; p <0.001)in the experimental group and it was not significant in the control group (8.19±30.82; p >0.15). Glycaemic status also significantly improve in experimentalgroup but not in control group. No major adverse events were observed in the two groups. Conclusion: These results were supportive of the renoprotective effects of HCQ in patients of DN. Therefore, we concludedthat HCQ can be an option in regression of DN in patients of DM. JCMCTA 2023 ; 34 (2) : 19-24